Flow behavior of skewed vortex generators on a backward-facing ramp - Cheawchan, Atcha-uea (2022)
The impact of skewness angle on the effectiveness of vortex generators (VGs) and the behavior of streamwise vortices on flow separation behind a backward-facing ramp (BFR) with a sharp transition were experimentally investigated using surface oil flow visualizations, planar and stereoscopic particle image velocimetry measurements. Counter/corotating streamwise vortices were generated by a set of boundary layer-type rectangular VG located upstream of the BFR that comprised a flat- and 30-inclined sections with different skewness angles of 10°, 20°, and 30°. Local Reynolds number based on the VG location was Rex ≈ 3 × 106. Results show that the reattachment length was reduced by ∼45% when the VG was located five times its height ahead of the transition. Additionally, the behavior of the vortex core generated by the left vane displayed strong dependence on the skewness angle, whereby its vorticity magnitude and vortex instability increase with the skewness angle. Circulation magnitude and vortex radius of the left vortex core are also observed to be physically larger and less stable. In contrast, the vortex core produced by the right vane displays opposite behavior as the skewness angle increases. Lastly, the vortex core location is observed to fluctuate more in the vertical direction than horizontal direction.